Meningkatkan Kemampuan Menentukan Nilai Tempat Bilangan Melalui Media Pohon Bilangan Bagi Siswa Gangguan Sepektrum Autisme - Nasution, Riska Sulastri; Mahdi, Arisul; Rahmahtrisilvia, Rahmahtrisilvia; Arnez, Gaby (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article discusses efforts to improve the ability to determine place value using number trees in students with autism spectrum disorder. This study used a quantitative approach with a single subject research (SSR) A-B design experimental method. The research subject was a student who had difficulty determining place value. Data collection techniques consisted of tests conducted during 15 meetings, consisting of 5 baseline phase meetings and 10 intervention phase meetings. Data analysis was performed visually using graphs to observe changes in the subject's performance. In the baseline phase, the student's completion rate was stable at 30%, 30%, 30%, 30%, 30%. After the intervention with the number tree media, there was a significant increase with the percentage of number place values ranging from 60%, 60%, 70%, 70%, 70%, 90%, 80%, 80%, 80%, 80%. The intervention was stopped after 10 meetings because the data showed a stable increase and met the criteria for successful intervention in SSR, namely that student performance was achieved and there were no indications of a decline (maintenance). The results of this study prove that the number tree media is effective in improving the ability to determine place value in students with autism spectrum disorder at SLB Al-Ikhlas Bukittinggi.